C-reactive protein in migraine sufferers similar to that of nonmigraineurs: The Reykjavik Study - Gudmundsson, Larus S (2009)
C-reactive protein (CRP), a marker of inflammation, has been associated with cardiovascular disease. Risk of cardiovascular disease is increased in migraineurs with aura. Results from a clinical report, case control- and a cohort study suggest that CRP is elevated in migraineurs compared to nonmigraineurs. We examined the proposed association in a case-control study nested within two large population-based studies. The relationship between migraine and CRP (hs-CRP) was studied in 5906 men and women age 55.0 (±8.5) years in the Reykjavik Study and 1345 men and women age 27.7 (±5.5) years from the Reykjavik Study for the Young. A modified version of the International Headache Society criteria was used to categorize people into migraineurs (2 or more symptoms) or nonmigraineurs. Migraineurs with visual or sensory symptoms were further defined as having migraine with aura (MA) or without aura (MO). Multivariable-adjusted CRP levels were similar in migraineurs and nonmigraineurs (0.83 vs. 0.79mg/l, p=0.44) for men and (0.87 vs. 0.87mg/l, p=0.90) for women. When further stratified by migraine aura and age, no differences were found between nonmigraineurs, MO and MA among men. In women MO, CRP was borderline higher than among nonmigraineurs and MA (1.01mg/l vs. 0.81 and 0.75mg/l, p=0.08 and p=0.08) in age group 19–34 years but significantly lower in age group 60–81 years (0.52mg/l vs. 1.07 and 1.01mg/l, p=0.007 and p=0.03). CRP levels were not increased among migraine sufferers compared to nonmigraineurs. Older women migraineurs without aura had lower CRP values compared to nonmigraineurs and migraineurs with aura.